Analysis of the Legal Validity of Oral Agreements Under Civil Law in Indonesia: Implications and Judicial Practices - Deanna Fitri Roshandi (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
In everyday life, agreements are frequently made without written documentation, especially in informal social interactions and economic activities. This raises important legal questions regarding the validity of verbal agreements. In Indonesia, the legal status of such agreements is governed by the Civil Code (KUHPerdata), particularly Article 1320, which outlines the requirements for the validity of an agreement. This article stipulates that an agreement must fulfill four conditions: consent, the capability of the parties, a certain subject matter, and a lawful cause. Despite the absence of written documentation, verbal agreements are considered legally valid in Indonesia as long as they meet these four requirements. The primary challenge, however, lies in the difficulty of proving the existence and terms of verbal agreements, particularly in cases of dispute. Since oral contracts lack physical evidence, parties involved may face difficulties in substantiating their claims in court. This makes verbal agreements vulnerable to legal challenges, as the burden of proof falls on the party asserting the agreement. In light of these challenges, it is advisable for parties involved in significant transactions or agreements to document their commitments in writing. A written agreement provides clear evidence of the terms and conditions agreed upon by the parties and serves as a safeguard in case of legal disputes. Although verbal agreements can hold legal weight, having written records is considered a better practice for ensuring legal protection and preventing potential conflicts. This study concludes that while verbal agreements are legally valid under Indonesian civil law, their enforceability can be compromised by the lack of written documentation, making written agreements a more secure option for all parties involved.